(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the legal views of the Islamic jurist Burhanuddin al-Marghinani on apostates (murtadd) and rebels (baghi) in the context of Islamic law. Based on his renowned legal treatise "al-Hidaya," the author examines how al-Marghinani interpreted legal, social, and governance matters concerning apostasy and rebellion. The article also highlights al-Marghinani’s contributions to the development of Islamic international law during the medieval period.